1981
DOI: 10.1073/pnas.78.8.5160
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of stimulation of prostaglandin synthesis by a factor from rheumatoid synovial tissue.

Abstract: [1-14C]AA levels in cultures of untreated cells. These observations are inconsistent with a mechanism of prostaglandin stimulation consisting of an increase in phospholipase activity, because this mechanism would increase free AA levels as well as prostaglandins. A mechanism is proposed in which free AA is maintained at low steady-state levels by reacylation of free AA into phospholipids at a rate more rapid than its reaction with cyclooxygenase to form prostaglandins. In this mechanism, stimulation ofthe rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Although PGE 2 is present, its levels are substantially lower than in adherent stellate dendritic cells. Other investigators and ourselves have subsequently found that media from cultured fragments of synovium (containing all cells including monocytemacrophages) can also stimulate PGE 2 production by synovial cell culture [160]. Furthermore, the same culture media can stimulate chondrocytes, bone-derived cells, and to a lesser extent certain skin fibroblasts.…”
Section: Control Of Collagenase Productionmentioning
confidence: 94%
“…Although PGE 2 is present, its levels are substantially lower than in adherent stellate dendritic cells. Other investigators and ourselves have subsequently found that media from cultured fragments of synovium (containing all cells including monocytemacrophages) can also stimulate PGE 2 production by synovial cell culture [160]. Furthermore, the same culture media can stimulate chondrocytes, bone-derived cells, and to a lesser extent certain skin fibroblasts.…”
Section: Control Of Collagenase Productionmentioning
confidence: 94%
“…Informed consent was obtained from every subject before the tissue samples were taken. Cultures were made by a modification of the method of Robinson et al (1975Robinson et al ( ,1981. The biopsy material was excised aseptically and immersed in Dulbecco minimal essential medium (DMEM) containing 25% fetal calf serum (FCS) (Gibco, Grand Island, NY), 100 U/ml penicillin, and 100 mg/ml streptomycin.…”
Section: Synovial Peritoneal and Skin Tissue Culturesmentioning
confidence: 99%
“…connective-tissue cells (fibroblasts and chondrocytes) to secrete proteinases and prostaglandins have been suggested to cause resorption of connectivetissue matrix, and their relationship to catabolin must be considered. Generally these factors have come from monocytes or macrophages (Deshmukh-Phadke et al, 1978, 1980Dayer et al, 1979;Ridge et al, 1980;Hamilton & Slywka, 1981) and synovial explants (Meats et al, 1980;Robinson et al, 1981). The best characterized is the monokine described by Dayer et al (1979), which stimulates synovial fibroblasts to produce collagenase and prostaglandins, and which is now thought to be interleukin 1 .…”
Section: Bars Represent +Semmentioning
confidence: 99%